Keamanan Dan Penyelesaian Sengketa Barang Milik Daerah Berupa Tanah Yang Dikuasai Pihak Ketiga Secara Sepihak - Muhammad Sultan Rahmadhani; Ansori Ansori (Program Studi Hukum Diluar Kampus Utama Universitas Pattimura Kabupaten Maluku Barat Daya, 2024)
Analysis of security aspects and resolving disputes over regional property in the form of land controlled unilaterally by third parties is an important issue in regional asset management. In many cases, regionally owned land can become the object of dispute when third parties control it illegally or without legal permission. Literature studies show that resolving these disputes often involves complex legal, administrative and social aspects. Security in the management of regionally owned land can be threatened by illegal land control practices, which can harm the community and local government. The dispute resolution process usually involves various steps, ranging from mediation, arbitration, to litigation in court. Effective resolution requires a holistic approach, including cooperation between local governments, law enforcement officials and local communities. In this context, it is important to implement clear regulations and strict monitoring mechanisms to prevent unilateral land control. The literature study also emphasizes the need for legal education and awareness among the community so that they can identify and report illegal land tenure, as well as understand their rights regarding land ownership.